OPTIMALISASI PEMBANGUNAN DESA MELALUI PELATIHAN PERENCANAAN PEMBANGUNAN DESA BAGI SEKRETARIS DESA - Hutagalung, Simon Sumanjoyo; Utoyo, Bambang; Sulistio, Eko Budi; Puspawati, Ani Agus (Prosiding Pengabdian FISIP Unila, 2012)
This Community Services  Activity  is being carried out  in South  Lampung District Jatiagung with  a lecture  and discussion  / FAQ. Meanwhile  evaluation design  used was  a quantitative  evaluation  through  pre test  and  post test.  Also  evaluated qualitatively  through  discussion  /  question and answer with  monitoring during  the extension / dissemination of the material presented during the process of counseling / socialization  takes place  between the  presenters  material  with participants socialization,  particularly with regard to  the aspects related to  Rural Development Planning. It can be concluded already understand the concept of Regional Planning and outline the content of their policies in the Indonesian Government regulations by members of the village in the district  secretaries  forum Jatiagung South Lampung regency. It has also been  understood mechanisms and  normative  regulations  in  Rural Development Planning  and the position of  rural   community participation  in the activities of  the Rural Development  Plan  by  the members of  the  village in the district  secretaries forum Jatiagung South Lampung regency. Keywords: Development Planning, Rural Assembly